Optimalisasi Pelayanan Santri melalui Model Pendampingan Capacity Building bagi Pengurus di Pesantren Sunan Drajat - Sunaji; Wanto; Wasis (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2026)
Sunan Drajat Islamic Boarding School, as an Islamic educational institution, has a strategic role in shaping the character and competencies of students, which is highly influenced by the quality of services provided by its administrators. This study aims to optimize student services through a capacity building-based mentoring model for boarding school administrators. The research design employs a collaborative participatory approach oriented toward action and continuous improvement. The methods include training, intensive mentoring, and evaluation based on structured instruments, involving 42 active administrators of Sunan Drajat Islamic Boarding School in Lamongan during the period of January–March 2025. The results indicate significant improvements in managerial competence (52% to 78%), interpersonal communication (58% to 82%), student satisfaction (49% to 71%), understanding of institutional vision (61% to 85%), and conflict management skills (44% to 69%). These findings demonstrate that capacity building-based mentoring is effective in improving the quality of administrators, which directly impacts the optimization of student services.